Production of 12-hydroxyeicosatetraenoic acid and vitamin E status in platelets from type I human diabetic subjects - Karpen, C.W; Cataland, S; O'Dorisio, T.M; Panganamala, R.V (Diabetes (New York, N.Y.), 1985)
Extract: Vitamin E content and biosynthesis of 12-hydroxyeicosatetraenoic acid (12-HETE) have been measured in platelets from type I diabetic subjects and age- and sex-matched, nondiabetic control subjects. Platelets from diabetic subjects synthesized significantly greater quantities of 12-HETE than did platelets from control subjects when 12-HETE synthesis was induced by thrombin or collagen, either in the presence or absence of indomethacin. Platelet conversion of exogenously added arachidonic acid (AA) to 12-HETE was not significantly different between the diabetic and control groups in the absence of indomethacin, although a small but significant increase in the conversion of AA to 12-HETE was present in the diabetic group platelets when indomethacin was added to the reaction. Vitamin E content was significantly reduced in platelets from the diabetic subjects, when compared with platelets from the control subjects, although plasma vitamin E levels were not significantly different between the two groups. Thrombin- and collagen-induced platelet 12-HETE synthesis demonstrated a significant negative linear correlation with platelet vitamin E content when measurements from both diabetic and control groups were combined. The above data suggest a relationship between low vitamin E content and increased 12-HETE synthesis in platelets from type I diabetic subjects.(author)